Analysis of essential oil of eaglewood tree (Aquilaria agallocha Roxb.) by gas chromatography mass spectrometry - Mohammad Nazrul Islam Bhuiyan; Jaripa Begum; Md. Nurul Huda Bhuiyan (Bangladesh Pharmacological Society, 2009)
The study was carried out to find out the differences in composition of oils obtained from healthy, naturally infected and artificially screws wounds eaglewood (Aquilaria agallocha Roxb.) using gas chromatography mass spectrometry (GC-MS) analysis. Natural healthy plants agar contained octacosane (19.83%), naphthalene, 1,2,3,5,6,7,8,8a-octahydro-1,8a-dimethyl-7-(1-methylethenyl)-, [1R-(1.alpha.,7.beta.,8a.alpha.)]- (12.67%), 5-isobutyramido-2-methyl pyrimidine (13.52%), caryophyllene oxide (11.25%) and (.+-.)-cadinene (5.46%). Natural infected plants agar (super agar) contained cycloheptane, 4-methylene-1-methyl-2-(2-methyl-1-propen-1-yl)-1-vinyl- (46.17%), caryophyllene oxide (33.00%) and 7-Isopropenyl-4a-methyl-1-methylenedecahydronaphthalene (20.83%). Artificially screw injected plants agar contained diisooctyl phthalate (71.97%), 1H-Cycloprop[e]azulen-4-ol, decahydro-1,1,4,7-tetramethyl-, [1ar-(1a.alpha.,4.beta.,4a.beta., 7.alpha., 7a.beta., 7b.alpha.)]- (9.16%), hexadecanoic acid (7.05%), naphthalene, 1,2,3,5,6,7,8,8a-octahydro-1,8a-dimethyl-7-(1-methylethenyl)-, [1R-(1.alpha.,7.beta.,8a.alpha.)]- (6.45%) and aristolene (5.36%). This study showed a marked difference in the oil compositions among the treatments with regards to their quality.